2021
DOI: 10.1101/2021.12.20.21268048
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Omicron mutations enhance infectivity and reduce antibody neutralization of SARS-CoV-2 virus-like particles

Abstract: The Omicron SARS-CoV-2 virus contains extensive sequence changes relative to the earlier arising B.1, B.1.1 and Delta SARS-CoV-2 variants that have unknown effects on viral infectivity and response to existing vaccines. Using SARS-CoV-2 virus-like particles (SC2-VLPs), we examined mutations in all four structural proteins and found that Omicron showed increased infectivity relative to B.1, B.1.1 and similar to Delta, a property conferred by S and N protein mutations. Thirty-eight antisera samples from individu… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
98
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(103 citation statements)
references
References 8 publications
4
98
0
1
Order By: Relevance
“…The lower level of protection could be attributed to the immune escape since several of the mutations in the Omicron are present in the area likely to bind neutralization antibodies and compromise the immune defence against Omicron ( Callaway and Ledford, 2021 ). Casirivimab and Imdevimab mAbs presented robust neutralization against Delta variant but remained ineffective against Omicron when assessed using a peusotyped SARS-CoV-2 virus-like particles having mutations in all four structural proteins ( Syed et al, 2022 ). A panel of anti-RBD mAbs encompassing S309 (parent mAb of sotrovimab), COV2-2196, COV2-2130 (parent mAbs of AZD8895, AZD1061), REGN10933, REGN10987, LY-CoV555 LY-CoV016 and Celltrion (CT-P59) intended for clinical use were tested for Omicron neutralization.…”
Section: Major Public Health Concerns Related To Omicronmentioning
confidence: 99%
See 1 more Smart Citation
“…The lower level of protection could be attributed to the immune escape since several of the mutations in the Omicron are present in the area likely to bind neutralization antibodies and compromise the immune defence against Omicron ( Callaway and Ledford, 2021 ). Casirivimab and Imdevimab mAbs presented robust neutralization against Delta variant but remained ineffective against Omicron when assessed using a peusotyped SARS-CoV-2 virus-like particles having mutations in all four structural proteins ( Syed et al, 2022 ). A panel of anti-RBD mAbs encompassing S309 (parent mAb of sotrovimab), COV2-2196, COV2-2130 (parent mAbs of AZD8895, AZD1061), REGN10933, REGN10987, LY-CoV555 LY-CoV016 and Celltrion (CT-P59) intended for clinical use were tested for Omicron neutralization.…”
Section: Major Public Health Concerns Related To Omicronmentioning
confidence: 99%
“…With pseudotyped Omicron particles bearing all the S mutation with HIV virus backbone, a lower entry efficacy and less proteases cleavage have been observed in Omicron, suggestive of low replicative efficacy in HEK293T cells or ACE2 receptor expressing A549 cells ( Hu et al, 2022 ). While using the SARS-CoV-2 virus-like particles (VLPs) harbouring all the mutations present in the four structural genes of Omicron revealed an increase in infectivity ( Syed et al, 2022 ). The difference in results between the pseudotyped Omicron particles ( Hu et al, 2022 ) that exhibit a lower entry efficacy and in SARS-CoV-2 like VLPs having Omicron like mutations that exhibited increased infectivity, possibly owing to the types of mutations incorporated in the said viruses and the cell line used for assay.…”
Section: Is the Severity For Omicron Is Less Than Its Other Voc Cousins?mentioning
confidence: 99%
“…The Omicron variant has turned out to be more contagious than any earlier coronavirus strains. The early research suggested that Omicron mutations enhance infectivity and reduce the neutralization of antibodies formed by prior infection or vaccination (11). Thus, rapid identification would help those patients at high risk of succumbing to COVID 19.…”
Section: The Studymentioning
confidence: 99%
“…The infection with the Omicron variant can boost and enhance more immune responses than other variants [254]. This means that having a previous natural infection or having the booster dose of vaccines was associated with partial protection against severe Omicron variant symptoms and hospital admissions [257,[259][260][261]. A previous COVID-19 infection and having two doses of vaccines can decrease the risk of hospital admission by 50% and 41%, respectively [261].…”
Section: B11529 (Omicron)mentioning
confidence: 99%